(3GdaJhMGJ GdecjI aj eYQaI CSQGQ GdeGdcjI hGdedcjIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3bGd Gddg JYGdi (B" (3dh cGf ai GdCQV edGFcI jeThf eWeFfjf s
(3BNQgG (B:s
(3dgPg GdETGQI aEfg MSfI LOkG ai hSHMGfg hdG jbHd JfRjg YHGOg aEfgG ai ZGjI GddWa hGdMSf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3HgG fXGe GdJYbjHIs
(3dHGH GdSGOS hGdSJhf ai eYQaI CSQGQ GdTQjYI XGgQkG hHGWfkG hCi GSe Edgi Ch LOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdeLGejYs